Role of Technology Integration in the Justice Management System - Galang Windi Pratama, Toebagus (Fakultas Hukum Universitas Widya Mataram, 2022)
The implementation of E-court based on Supreme Court Regulation Number 3 of 2018, according to the author, its effectiveness is still in doubt because of the drastic change from the previous court service system which was completely offline but now must be done online, of course, it leads to its own polemic which is not impossible, it actually slows down the trial. Based on this, the author intends to conduct research that examines the role of technology integration in the justice system. The research was conducted using an empirical juridical approach, namely descriptive where the research source relies on data taken in the field where in this case the author chooses to conduct research at the Semarang City District Court and the Religious Courts which are supported by relevant literature. analyzed using data triangulation to obtain relevant results. The results show that the integration of technology in the judicial system as seen in the application of e-Court in Semarang is still not effective because based on data obtained from 2016-2019 there is no significant increase in applicants registering cases. E-Court still needs a lot of improvement including adding the possibility to integrate the e-court system into criminal justice. However, before achieving that, there is a big task that must be completed by the Supreme Court as the institution that oversees all judiciary in Indonesia, namely increasing socialization not only to advocates but also court employees and the public as potential application users so that the implementation of e-court can run effectively. Keywords: Technology Integration, Justice System.